1999
DOI: 10.1002/(sici)1099-1581(199903)10:3<157::aid-pat857>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

The self-diffusion of macromolecules in binary blends of poly(ethylene glycol)

Abstract: The concentration and molecular mass dependencies of the self‐diffusion coefficients were obtained for higher molecular mass component in binary blends of the homopolymer poly(ethylene glycol) (PEG) by a nuclear magnetic resonance method with pulsed magnetic field gradient. The shape of the diffusion decay and its dependence on the diffusion observation time in binary PEG blends have been investigated. The experimental results were explained by hypothesizing the existence of cluster formation in polymer melts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In addition, because α-casein does not form a stable and well-folded structure, the influence of internal dynamics on its diffusion coefficient could be expected. Previously, it has been shown that this contribution is not significant for the construction of master curves for the concentration dependence of diffusion coefficients of globular proteins and poly­(ethylene glycol) homopolymers but becomes important in the case flexible polymers and poly­(allylcarbosilane) dendrimers . On the basis of experimental data obtained for 17 different polymer–solvent systems, it was shown that the contribution of internal dynamics to the diffusion coefficient can be excluded by dividing the polymer diffusion coefficient by the dimensionless normalizing function L (φ) obtained from the concentration dependences of the polymer T 1 and T 2 relaxation times .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, because α-casein does not form a stable and well-folded structure, the influence of internal dynamics on its diffusion coefficient could be expected. Previously, it has been shown that this contribution is not significant for the construction of master curves for the concentration dependence of diffusion coefficients of globular proteins and poly­(ethylene glycol) homopolymers but becomes important in the case flexible polymers and poly­(allylcarbosilane) dendrimers . On the basis of experimental data obtained for 17 different polymer–solvent systems, it was shown that the contribution of internal dynamics to the diffusion coefficient can be excluded by dividing the polymer diffusion coefficient by the dimensionless normalizing function L (φ) obtained from the concentration dependences of the polymer T 1 and T 2 relaxation times .…”
Section: Resultsmentioning
confidence: 99%